2006
DOI: 10.1063/1.2185634
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation rate measurements of 1-propanol in helium: The effect of carrier gas pressure

Abstract: Kinetics of homogeneous nucleation in supersaturated vapor of 1-propanol was studied using an upward thermal diffusion cloud chamber. Helium was used as a noncondensable carrier gas and the influence of its pressure on observed nucleation rates was investigated. The isothermal nucleation rates were determined by a photographic method that is independent on any nucleation theory. In this method, the trajectories of growing droplets are recorded using a charge coupled device camera and the distribution of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…For instance, most experiments have reported that the nucleation rate increases with decreasing total pressure, even if temperature and supersaturation ratios are both kept constant. This has been recently confirmed on measurements for the 1-propanol nucleation in helium gas [83], but is at variance with older experiments on n-butanol [87]. Needless to say, such effects induced by the environment should be taken into account when comparing experiment and theory, but they present significant additional difficulties.…”
Section: Nucleation Rate Vs Supersaturation and Temperaturementioning
confidence: 70%
See 2 more Smart Citations
“…For instance, most experiments have reported that the nucleation rate increases with decreasing total pressure, even if temperature and supersaturation ratios are both kept constant. This has been recently confirmed on measurements for the 1-propanol nucleation in helium gas [83], but is at variance with older experiments on n-butanol [87]. Needless to say, such effects induced by the environment should be taken into account when comparing experiment and theory, but they present significant additional difficulties.…”
Section: Nucleation Rate Vs Supersaturation and Temperaturementioning
confidence: 70%
“…(8), using appropriate values for the surface tension and liquid density. Remaining discrepancies of 20-40% in the critical size have been reported, depending on the nature of the fluid [81][82][83].…”
Section: Nucleation Rate Vs Supersaturation and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…According to Krejčí (2010), the saturators allow stable and repeatable saturated vapour generation in the range of parameters defined in Table 1. various devices is the mechanism used to achieve the supersaturated state of the system. The supersaturation can be reached by diffusion of the nucleating vapours (Ball et al, 1999;Benson et al, 2008;Benson et al, 2009;Berndt et al, 2010;Benson et al, 2011;Brus et al, 2011) or by cooling the vapours by either temperature gradient (Katz and Ostermier, 1967;Brus et al, 2005;Herrmann et al, 2010;Zollner et al, 2012;Travnickova et al, 2013) or adiabatic expansion (Wagner and Strey, 1981;Peters, 1982;Viisanen and Strey, 1994). The binary nucleation of H 2 SO 4 -H 2 O presents the most important atmospheric nucleation system (Benson et al, 2008).…”
Section: Mixture Preparation Devicementioning
confidence: 99%
“…However, the effect of the carrier-gas pressure on nucleation was not observed in previous experiments with the expansion cloud chambers. [6][7][8][9] Moreover, in some experiments the effect of the carrier gas pressure was shown to be negative, [1][2][3][4][5][10][11][12] that is, the carrier gas reduced the rate of nucleation, while in some other experiments the effect was shown to be positive. [13][14][15] The apparent conflicting results from different experiments called for more molecular-level investigations of the carrier-gas effect.…”
Section: Introductionmentioning
confidence: 99%